(untitled) (Environment & Health, 2016)
The first place among the factors that adversely affect the level of health of the population in the Ukraine is given by the experts in the area of the health and environment to the water, which is ahead in this among atmospheric air and food. Taking into consideration above mentioned, the objective of our research was the hygienic substantiation of necessity and ways of municipal centralized water supply systems’ modernization in the Ukraine to reduce the level of uninfectious morbidity. Materials and methods. To achieve this goal in our research the following methods were used: bibliographic method of scientific information analysis, forecasting methods and calculations, the method of sanitary inspection of the technological equipment, the organoleptic, chemical, physical-chemical, hydro-biological, electrochemical, technological, methods of researches. Results. The direction and pace of cancer risk factors changes and cancer morbidity dynamics of the population in the Ukraine were studied. It was established that one of the main reasons for the increase of cancer rates in the Ukraine is the deterioration in the quality of water supplied to the end users by centralized water supply systems, first of all, due to the content of chlorinorganic compounds (COC below) in it. Link between corrosive aggressivness and stability of drinking water of filtration station of water purification facilities of public utility “Nikopol operational department of water supply and sewerage economy” and intensity of the COCs formation on the stages of its purification and during transportation in pipelines. It was established that purify drinking water and to supply by it end-users in any point of the water distribution network with quality meeting the requirements of State sanitary rules and standards 2.2.4 - 171 -10 or other normative documents is possible only in case of sufficient level of coagulation and further stabilization processing of water before it enters the water distribution network.